2008
DOI: 10.1186/1743-422x-5-120
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Measles Viruses in China, 2004

Abstract: Genetic characterization of wild-type measles virus was studied using nucleotide sequencing of the C-terminal region of the N protein gene and phylogenetic analysis on 59 isolates from 16 provinces of China in 2004. The results showed that all of the isolates belonged to genotype H1. 51 isolates were belonged to cluster 1 and 8 isolates were cluster 2 and Viruses from both clusters were distributed throughout China without distinct geographic pattern. The nucleotide sequence and predicted amino acid homologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…1b). When including reference sequences of H1 subtypes described previously in China [Yu et al, 2007;Zhang et al, 2007Zhang et al, , 2008Zhang et al, , 2009bJi et al, 2009], it was observed that all H1 strains detected in Hong Kong between 2006 and 2009 belonged to subtype H1a or cluster 1 (Fig. 1b).…”
Section: Genotypingmentioning
confidence: 87%
“…1b). When including reference sequences of H1 subtypes described previously in China [Yu et al, 2007;Zhang et al, 2007Zhang et al, , 2008Zhang et al, , 2009bJi et al, 2009], it was observed that all H1 strains detected in Hong Kong between 2006 and 2009 belonged to subtype H1a or cluster 1 (Fig. 1b).…”
Section: Genotypingmentioning
confidence: 87%
“…Analysis of the H protein sequences currently published in GenBank revealed that L397 was restricted to genotype H1, the MeV genotype predominantly circulating in China. More than 109 000 cases were reported from China in 2007, representing 39 % of the global measles cases (Bian et al, 2006;Liffick et al, 2001;Xu et al, 1998;Yu et al, 2007;Zhang et al, 2008). H1 has also been observed in Korea and Japan (Na et al, 2003;Nakayama et al, 2003;Tomita, 2006;Zhou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting that the molecular epidemiological pattern of rubella viruses in China appears to be quite different from those of the measles virus (30,33), mumps virus (6), human enterovirus 71 (32), and coxsackievirus A16 (31). Virological surveillance for measles virus and mumps virus since 1995 shows that the genotype H1 of measles virus and genotype F of mumps virus are the only genotypes found thus far in China, and subgenotype C4 of human enterovirus 71 and genotype B1 of coxsackievirus A16 have been continuously circulating in China since they were first detected in 1998 and 1999, respectively.…”
Section: Discussionmentioning
confidence: 99%